S.O.S. Pinna nobilis: A Mass Mortality Event in Western Mediterranean Sea - Vázquez-Luis, Maite; Álvarez, Elvira; Barrajón, Agustín; García-March, José R.; Grau, Amalia; Hendriks, Iris E.; Jiménez, Santiago; Kersting, Diego; Moreno, Diego; Pérez, Marta; Ruiz, Juan M.; Sánchez, Jordi; et al. (Frontiers in Marine Science, 2017)
A mass mortality event impacting the bivalve Pinna nobilis was detected across a wide geographical area of the Spanish Mediterranean Sea (Western Mediterranean Sea) in early autumn 2016. Underwater visual censuses were conducted across several localities separated by hundreds of kilometres along the Spanish Mediterranean coasts and revealed worrying high mortality rates reaching up to 100% in the center and southernmost coasts of the Iberian Peninsula including Balearic Islands. Populations on the northern coasts of the Spanish Mediterranean Sea seemed to be unaffected (Catalonian region). Histological examination of affected individuals revealed the presence of a haplosporidan-like parasite within the digestive gland being probably the pathogen that causes this mortality. The present mass mortality event has spread rapidly, causing high mortality rates in infected populations. Taking into account the degree of impact, the geographic extent, and the high probability that the infection is still in a spreading phase; this might be considered the largest mass mortality event ever registered for P. nobilis up to date, forcing this emblematic bivalve into a critical viability status over hundreds of kilometers of coast.